Introduction of design culture as approach in endogenous regional development: a study case in farming community of Sabrang Village, Central Java, Indonesia. Issue 1 (November 2021) - Purwandaru, P; Utami, L A; Ueda, A; Ardianto, D T
Abstract: Within Design Science, Design Culture is a branch focused on regional development through design principles and participatory tools designed to intrinsically understand endogenous potentials. Designing living is a goal/output based on recognizing regional "color" and facilitating the community for economic sustainability, social acceptability, and environmental soundness. Anthropological/ethnographic study embodied in material culture research is applied practically in learning about life in the field to incite curiosity and learning reflexes. In experiencing communal living, student-participants Observe-Collect-Map valuable tangible/intangible potentials (treasures), and analyses for presentations, ideate visions and co-design with local community as one of stakeholders. As an example, UNS-FSRD Design Culture Laboratory collaborates with UNS-Agriculture Faculty and GAPOKTAN Sedyo Makmur to redevelop Rojolele Delanggu Rice and community-based plantations in Sabrang Village, Delanggu.